Semantic and syntactic problems in using relative clauses in English of Yendinh High school students = Những vấn đề về ngữ nghĩa và cú pháp trong sử dụng mệnh đề quan hệ tiếng Anh của học sinh trường Yên Định. M.A Thesis Linguistics: 60 14 10 - Trịnh, Đình Lan (University of Languages and International Studies, 2017)
M.A. Thesis. Methodology -- University of Languages and International Studies. Vietnam National University, Hanoi, 2011